Efficacy of acupuncture for primary osteoporosis: a systematic review and meta-analysis of randomized controlled trials - Tianyi Ma; Tiantian Zhang; Le Zhang; Haoming Zhao; Ke Liu; Jianjun Kuang; Liang Ou (Journal of Orthopaedic Surgery and Research)
Abstract Background Primary osteoporosis (POP) is a common metabolic bone disorder that has a devastating effect on their quality of life in patients. Acupuncture, a traditional Chinese therapy, has been used to treat osteoporosis for over 2000 years. This study aimed to determine the efficacy of acupuncture in treating POP compared to conventional medicine or placebo. Methods We searched for potentially relevant studies in PubMed, Web of Science, Embase, Cochrane Central Register of Controlled Trials, China National Knowledge Infrastructure, China Biology Medicine disc, Wanfang database and ClinicalTrials.gov up to December 20, 2024. Randomized controlled trials investigating treatment of POP for which acupuncture was administered as a stand-alone treatment or combined with conventional medicine compared to conventional medicine or placebo, were included. The outcomes included bone mineral density (BMD), visual analogue scale (VAS) scores, clinical effectiveness rate, estradiol (E2), Oswestry Disability Index (ODI), and levels of serum alkaline phosphatase (ALP). Data were synthesized using a random-effects meta-analysis model, and the observed heterogeneity was investigated using subgroup analyses. Study quality was appraised using the Cochrane RoB 2 tools, and the quality of the aggregated evidence was evaluated using the GRADE guidelines. Publication bias was assessed by funnel plots and validated by Egger's test. Results Forty eligible articles with 2654 participants were identified. Compared to the control group, acupuncture effectively increased the BMD (MD 0.04 [0.03–0.06], P < 0.001, I 2 = 92%), clinical efficacy (RR 1.24 [1.14–1.34], P < 0.001, I 2 = 81%), and levels of E2 (SMD 0.30 [0.09–0.52], P = 0.006, I 2 = 0%), and reduced the VAS scores (SMD − 1.79 [− 2.29 to − 1.29], P < 0.001, I 2 = 95%). Data on ODI and ALP were insufficient for meta-analysis. Conclusion The current evidence suggests that the efficacy of acupuncture in improving the symptoms of POP are encouraging for its use in clinical practice as a physical intervention for patients with POP. However, since the included patients were all from China, there was a risk of sample bias, high-quality multicenter studies in different countries or regions should be conducted in the future.